PREPARATION AND CHARACTERIZATION OF CEFTRIAXONE SODIUM ENCAPSULATED CHITOSAN NANOPARTICLES - Manimekalai, P.; Dhanalakshmi, R.; Manavalan, R. (International Journal of Applied Pharmaceutics, 2017)
Objective: The objective of this study was to prepare ceftriaxone sodium chitosan nanoparticles (CS-NP) from different drug and polymer ratios and analyze their physicochemical characteristics. Methods: Ceftriaxone sodium loaded chitosan nanoparticles were prepared using chitosan as a polymer and tri sodium polyphosphate (TPP) as cross linking agent by ionic cross linking and coacervation with the aid of sonication. Various trials have been carried out for the confirmation of nanoformulation. Parameters such as the zeta potential, polydispersity, particle size, entrapment efficiency, in vitro drug release Thermo gravimetric analysis and scanning electron microscope of the nanoparticles were assessed for confirmation of nanoformulation. Results: The formulated nanoparticles showed mean particle size, polydispersity index and zeta potential to be 183.1±8.42 nm, 0.212±0.05, +38.5±1.6 mV respectively and the drug loading was found to be 46.42±10 %. In vitro drug release was showed a biphasic release pattern with initial burst release followed by sustained release of formulated nanoparticles. The cumulative percentage of drug release was about 83.08 %. Conclusion: Formulation F2 was found to be the best formulation with a higher cumulative percentage of drug release. Modified ionic gelation method can be utilized for the development of chitosan nanoparticles of ceftriaxone sodium. Polymer and crosslinking agent concentrations and sonication time are rate-limiting factors for the development of the optimized formulation. The chitosan nanoparticles developed would be capable of sustained delivery of ceftriaxone sodium.